Phonemic Fluency in Portuguese-speaking Subjects in Brazil: Ranking of Letters - Senhorini, Maurien C.T.; Amaro Júnior, Edson; de Mello Ayres, Adriana; de Simone, Adriana; Busatto, Geraldo F. (Journal of clinical and experimental neuropsychology, 2006)
Phonological verbal fluency studies in English most commonly employ the letters F-A-S as stimuli. We assessed the production of words with these and 14 other letters in Portuguese-speaking healthy subjects (n = 74). The letters F-A-S were ranked among the easiest to produce words in one minute, which is consistent with the findings of studies with English-speaking subjects. There were differences in the overall ranking of letters depending on whether the total word number or the latency between words were considered. Our findings provide a databank of phonological verbal fluency performance using different stimuli in Portuguese, and demonstrate that the ranking of the letters F-A-S is comparable between the English and Portuguese languages in terms of the level of difficulty to produce words, when the task is used in its traditional format.